The Effect of RoA, Roe, and DeR on Stock Prices in Companies That Listed on the LQ-45 Indonesia Stock Exchange in the 2018-2020 Period - Laia, Roslina; Sitorus, Friska Darnawaty; Hasan, Wahyudin (CV. Rayyan Dwi Bharata, 2023)
This study analyzes the effect of Return on Assets, Return on Equity, and Debt to Equity Ratio on stock prices in LQ-45 companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The sample used consisted of 63 companies consisting of 21 companies from 45 companies listed in the LQ45 index during that period. The analytical tool used is multiple linear regression analysis with purposive sampling. The results of the study show that together, Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity (DER) have a significant influence on stock prices. Partially ROA and ROE do not affect stock prices, while DER affects stock prices.